2019
DOI: 10.1371/journal.pone.0223243
|View full text |Cite
|
Sign up to set email alerts
|

Demographic characteristics, site and phylogenetic distribution of dogs with appendicular osteosarcoma: 744 dogs (2000-2015)

Abstract: ObjectiveTo report demographic characteristics of a contemporary population of dogs with appendicular osteosarcoma and assess the relationship between demographic characteristics, site distribution, and phylogenetic breed clusters.DesignRetrospective case series.MethodsA search of the Veterinary Medical Database was performed for dogs with appendicular osteosarcoma as a new diagnosis. Entries were reviewed for the sex, neuter status, age at diagnosis, breed, affected limb, and tumor location. The reported bree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 37 publications
8
51
3
Order By: Relevance
“…Pathological fracture is reported to occur in 38% of osteosarcoma cases [ 2 , 3 ]. Treatment for osteosarcoma can include amputation of the affected limb or resection of axial lesions, and adjuvant chemotherapy may be recommended [ 2 , 4 , 5 ]. However, osteosarcoma often undergoes early haematogenous spread and, whilst just 10% of canine osteosarcoma cases present with gross metastases, 90% have been shown to possess microscopic metastatic disease at the time of diagnosis [ 1 , 2 , 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological fracture is reported to occur in 38% of osteosarcoma cases [ 2 , 3 ]. Treatment for osteosarcoma can include amputation of the affected limb or resection of axial lesions, and adjuvant chemotherapy may be recommended [ 2 , 4 , 5 ]. However, osteosarcoma often undergoes early haematogenous spread and, whilst just 10% of canine osteosarcoma cases present with gross metastases, 90% have been shown to possess microscopic metastatic disease at the time of diagnosis [ 1 , 2 , 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several dog breeds are reportedly predisposed to osteosarcoma, including the Rottweiler, Irish Wolfhound, Greyhound and Golden Retriever, and it has been shown that predisposition to osteosarcoma has a genetic basis in dogs [ 4 , 5 , 10 13 ]. The majority of at-risk breeds possess large body mass, and fewer than 5% of osteosarcoma cases are reported in dogs under 15 kg [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, polyostotic presentation was also described in a domestic dog, which had multiples sites of neoplastic growth in the appendicular skeleton and also had kidney metastasis [ 31 ]. In domestic animals, osteosarcoma usually results in metastasis, which frequently affects the lungs, kidney, and liver [ 4 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Less frequently, this tumor may be primary of soft tissues when it is classified as an extra-skeletal form [ 1 3 ]. Among domestic animals, osteosarcoma affects mainly dogs and cats between 8 and 10 years of age, with poor prognosis, and a high metastatic rate [ 4 6 ]. In birds, osteosarcoma is uncommon and there are only a few cases reported in domestic and wild species [ 7 9 ], in which it may arise in the axial or, more commonly, in the appendicular skeleton [ 7 , 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Binary logistic regression modelling was executed using the glm-logit function in the R-stats package to determine univariable associations between risk factors (purebred-status, breed, Kennel Club breed group, body mass, age, sex/neuter, dachshund-status, spaniel-status, chondrodystrophy-status and skull-shape) and osteosarcoma [70]. Univariable evaluation showed that the median age of cases (8.50 years, IQR 6.58-10.50) was higher than non-cases ( Because breed was a factor of primary interest for the study, variables derived from the breed information were tested for collinearity using a VIF score available in the caret package [64,[71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%